GNATHOPLEURA QUADRIDENTATA (HIYMENOPTERA: BRACONIDAE: ALYSIINAE), A NEW NATURAL ENEMY OF PECKIA CHRYSOSTOMA (WIEDEMANN) (DIPTERA: SARCOPHAGIDAE) IN BRAZIL - Marchiori, Carlos Henrique; Silva Filho, Otacílio Moreira; Fortes, Francilene Cardoso Alves; Gonçalves, Patrícia Luzia Pereira; Brunes, Rélia Rodrigues; Laurindo, Juliana Fischer; Borges, Rauer Ferreira (Revista de Patologia Tropical / Journal of Tropical Pathology, 2008)
This note reports for the first time the occurrence of the parasitoid Gnathopleura quadridentata (Hymenoptera: Braconidae: Alysiinae) parasitizing pupae of Peckia chrysostoma (Wiedemann) (Diptera: Sarcophagidae) in Brazil. The flues were collected with traps baited with bovine liver in a wooded area in the vicinity of the Parque da Serra de Caldas Novas, Goiás, from September to December, 2003. A total of four specimens of the parasitoid G. quadridentata were reared from a total of 65 pupae of P. chrysostoma.